2014
DOI: 10.1016/j.actamat.2014.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation glide-controlled room-temperature plasticity in 6H-SiC single crystals

Abstract: In situ transmission electron microscopy observations of uniaxial compression of sub-300 nm diameter, cylindrical, single-crystalline 6H-SiC pillars oriented along h0 0 0 1i and at 45°with respect to h0 0 0 1i reveal that plastic slip occurs at room-temperature on the basal {0 0 0 1} planes at stresses above 7.8 GPa. Using a combination of aberration-corrected electron microscopy, molecular dynamics simulations and density functional theory calculations, we attribute the observed phenomenon to basal slip on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…The first way is the glide mode, i.e., shear occurred inside the bilayers and the second way is the shuffle mode, i.e., shear occurred between two bilayers. However, the results of electronic structure calculations with density functional theory suggested that the basal slip on the shuffle set dislocation along the < 1 100 > direction does not dissociate into partials separated by a stacking fault due to lack of an intermediate energy minimum along this path [44]. Therefore the observed twins in this work should be originated from the glide set along the < 1100 > direction.…”
Section: Formation Mechanisms Of Sfs and Twinningmentioning
confidence: 83%
“…The first way is the glide mode, i.e., shear occurred inside the bilayers and the second way is the shuffle mode, i.e., shear occurred between two bilayers. However, the results of electronic structure calculations with density functional theory suggested that the basal slip on the shuffle set dislocation along the < 1 100 > direction does not dissociate into partials separated by a stacking fault due to lack of an intermediate energy minimum along this path [44]. Therefore the observed twins in this work should be originated from the glide set along the < 1100 > direction.…”
Section: Formation Mechanisms Of Sfs and Twinningmentioning
confidence: 83%
“…Once plasticity was activated, the size effect was similar to BCC metals for MgO soft slip systems, while hard slip systems showed a behavior rather similar to GaAs [25] and Si micropillars [26]. Deformation by dislocation glide during micropillar compression could also be activated at room temperature in high strength ceramic monocrystals like sapphire [27], silicon carbide [28] and silicon nitride [29]. With respect to zirconia, Lai and co-workers [30] have recently shown that single-crystal or oligocrystalline micropillars of zirconia highly doped with Ce and Y can display shape memory and superelastic effects in association with phase transformation under compression, while the presence of other plastic phenomena has not been discussed.…”
Section: Introductionmentioning
confidence: 78%
“…The activation of dislocation movement at room temperature does not normally occur in bulk ceramic specimens without confinement. This is no longer valid at the small scale, where, for example, monocrystals of alumina, chromia, silicon carbide and silicon nitride [27][28][29]48] have been deformed plastically under compression by slip. The participation of dislocation glide is likely to happen here since the stress level reached without fracture is comparable to that in confined deformation by grinding, where dislocation activity is dominant [49].…”
Section: Loading-unloading Tests At Increasing Peak Stressmentioning
confidence: 99%
“…Young's modulus decreases approximately linearly as the cross-section area of a cantilever beam becomes smaller. The bulk modulus of SiC is cited as > 415 GPa [8]. Among our measurements, the highest Young's modulus, 393.98 GPa, was measured from beams with a cross-sectional of 1.18 µm 2 , and the lowest, 187.84 GPa, from those with a cross sectional area of 0.086 µm 2 .…”
Section: Methods / Materialsmentioning
confidence: 88%